Resilient Economics Education Ecosystem: A Scoping Review of Teaching and Learning Strategies in South African Schools - Nana Yaw Brenya Agyeman; Menu Elijah Osei (ILIN Institute Makassar, 2026)
The study explores strategies to foster a resilient Economics education ecosystem that addresses resource limitations and capacity constraints in South African schools. Economics education faces systemic, pedagogical, and contextual challenges that reduce instructional quality. This hinders student engagement and limits the development of critical thinking skills. Strengthening the educational ecosystem is therefore critical to improving teaching and learning outcomes. This study employed a systematic review of coping strategies, mapping peer-reviewed articles, grey literature, and reports published between 2020 and 2025. A total of 40 studies met the inclusion criteria and were analysed to identify patterns in factors influencing Economics instruction. Findings highlight the centrality of teacher expertise, supported by ongoing professional development and collaboration, in enhancing instructional resilience. Adequate infrastructure and learning resources facilitate students’ conceptual understanding, while inequalities in schools constrain learning conditions. Effective leadership and adherence to policy further support instructional delivery, motivation, and curriculum implementation. The study concludes that a resilient instructional ecosystem requires coordinated support across its components to strengthen classroom and school environments and enhance students’ understanding of Economics content. These insights inform instructional and policy strategies, guide resource allocation, and promote innovative pedagogies. The study contributes to sustainable, high-quality Economics education in South African schools.